Two new species of the genus Episcaphium Lewis (Coleoptera, Staphylinidae, Scaphidiinae) of China - Sheng, Chun; Gu, Fu-Kang (Zootaxa, 2009)
The genus Episcaphium Lewis, 1893 is a small Asian genus of Scaphidiinae. It can be distinguished from related genera by the combination of the following characters: body robust, head with occipital region visible, eye notched, segments of antennal club symmetrical, scutellum large and visible, procoxal cavities closed posteriorly, basal pronotal angle not prolonged apically, base of elytron not impressed, elytral disc with or without puncture rows but never with puncture striae; metaventrite glabrous in both sexes.